SPECIFIC CHARACTERISTICS OF THE FORMATION OF PROFESSIONAL COMPETENCE IN EDUCATORS - O‘razov Baxtiyor Haydarovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the concept of competence, professional competence, competent approach, professionally competent teacher, some things that need to be done if the formation of professional competence of future pedagogues is considered as a pedagogical problem, the concept of competence in professional competence and it is said that future pedagogues need to pay attention to the forms of theoretical training in the formation of professional competence.